Recent advancements in the breeding of sorghum crop: current status and future strategies for marker-assisted breeding - Baloch, Faheem Shehzad; Altaf, Muhammad Tanveer; Liaqat, Waqas; Bedir, Mehmet; Nadeem, Muhammad Azhar; Cömertpay, Gönül; Çoban, Nergiz; Habyarimana, Ephrem; Barutçular, Celaleddin; Cerit, Ibrahim; Ludidi, Ndomelele; Karaköy, Tolga; et al. (Frontiers in Genetics, 2023)
Sorghum is emerging as a model crop for functional genetics and genomics of tropical grasses with abundant uses, including food, feed, and fuel, among others. It is currently the fifth most significant primary cereal crop. Crops are subjected to various biotic and abiotic stresses, which negatively impact on agricultural production. Developing high-yielding, disease-resistant, and climate-resilient cultivars can be achieved through marker-assisted breeding. Such selection has considerably reduced the time to market new crop varieties adapted to challenging conditions. In the recent years, extensive knowledge was gained about genetic markers. We are providing an overview of current advances in sorghum breeding initiatives, with a special focus on early breeders who may not be familiar with DNA markers. Advancements in molecular plant breeding, genetics, genomics selection, and genome editing have contributed to a thorough understanding of DNA markers, provided various proofs of the genetic variety accessible in crop plants, and have substantially enhanced plant breeding technologies. Marker-assisted selection has accelerated and precised the plant breeding process, empowering plant breeders all around the world.